Can CO2 emissions cease growing in Côte d'Ivoire? An empirical analysis of the effects of economic growth, energy consumption, industrialization, and urbanization in the presence of structural breaks - Iritie, Bi Goli Jean Jacques; Tiemele, Jean Baptiste (Asian Journal of Economic Modelling, 2024)
This paper aims at examining the effects of economic growth, energy use, industrialization, and urbanization on carbon dioxide (CO2) emissions in Côte d'Ivoire over the period from 1970 to 2016. It also analyzes the conditions under which these emissions can cease growing. We used cointegrating regression models, like the fully modified ordinary least square (FMOLS), the canonical cointegration regression (CCR), and the dynamic ordinary least square (DOLS), to figure out the long-run coefficients. The vector error correction model (VECM) is used in the causality analysis. Finally, we carried out an analysis of the conditional thresholds for reducing CO2 emissions. The results indicate that there is a long-term, significant positive relationship between economic growth, energy use, urbanization, and industrialization, as well as carbon dioxide emissions, in the presence of structural breaks. In other words, they increase CO2 emissions in Côte d'Ivoire. The causality analysis results reveal a long-term bidirectional causal link between industrialization and CO2 emissions, as well as long-term unidirectional causal links from each independent variable to CO2 emissions. The conditional threshold analysis for reducing CO2 emissions shows that under the current economic conditions of the country, pollution will continue to increase. Our findings corroborate the conclusions of COP28, the most recent United Nations conference on climate change. Therefore, a good carbon dioxide pricing or taxation policy for polluting industries, law enforcement and regulations, and the implementation of effective strategies for the promotion and development of clean and renewable energy use will effectively reverse the trend in Côte d'Ivoire.